The MATH-BTB Protein TaMAB2 Accumulates in Ubiquitin-Containing Foci and Interacts With the Translation Initiation Machinery in Arabidopsis - Bauer, Nataša; Škiljaica, Andreja; Malenica, Nenad; Razdorov, Genadij; Klasić, Marija; Juranić, Martina; Močibob, Marko; Sprunck, Stefanie; Dresselhaus, Thomas; Leljak Levanić, Dunja (Frontiers in Plant Science, 2019)
MATH-BTB proteins are known to act as substrate-specific adaptors of CUL3-based E3 ligases in the ubiquitin proteasome pathway. Their BTB domain binds to CUL3 scaffold proteins and the less conserved MATH domain targets a highly diverse collection of substrate proteins to promote their ubiquitination and subsequent degradation. In plants, a significant expansion of the MATH-BTB family occurred in the grasses. Here, we report analysis of TaMAB2, a MATH-BTB protein transiently expressed at the onset of embryogenesis in wheat. Due to difficulties in studying its role in zygotes and early embryos, we have overexpressed TaMAB2 in Arabidopsis to generate gain-of-function mutants and to elucidate interaction partners and substrates. Overexpression plants showed severe growth defects as well as disorganization of microtubule bundles indicating that TaMAB2 interacts with substrates in Arabidopsis. In tobacco BY-2 cells, TaMAB2 showed a microtubule and ubiquitin-associated cytoplasmic localization pattern in form of foci. Its direct interaction with CUL3 suggests functions in targeting specific substrates for ubiquitin-dependent degradation. Although direct interactions with tubulin could not be confimed, tandem affinity purification of TaMAB2 interactors point towards cytoskeletal proteins including tubulin and actin as well as the translation initiation machinery. The idenification of various subunits of eucaryotic translation initiation factors eIF3 and eIF4 as TaMAB2 interactors indicate regulation of translation initiation as a major function during onset of embryogenesis in plants.